2021
DOI: 10.1038/s41598-021-89856-3
|View full text |Cite
|
Sign up to set email alerts
|

Tubulin binding potentially clears up Bortezomib and Carfilzomib differential neurotoxic effect

Abstract: Proteasome inhibitors (PIs) represent the gold standard in the treatment of multiple myeloma. Among PIs, Bortezomib (BTZ) is frequently used as first line therapy, but peripheral neuropathy (PN), occurring approximately in 50% of patients, impairs their life, representing a dose-limiting toxicity. Carfilzomib (CFZ), a second-generation PI, induces a significantly less severe PN. We investigated possible BTZ and CFZ off-targets able to explain their different neurotoxicity profiles. In order to identify the pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 34 publications
(46 reference statements)
0
6
0
Order By: Relevance
“… 5 Similarly, in vitro data showed that bortezomib is also able to enhance tubulin polymerisation 16 and disrupt axonal transport, 17 while the non-neurotoxic proteasome inhibitor carfilzomib has no effect on microtubules at antineoplastic concentrations. 18 Further, bortezomib has been linked to delta 2 tubulin accumulation, altering microtubule stability and dynamics with consequent axonopathy and altered mitochondria motility. 19 Notably, neurographic in vivo molecular imaging demonstrated axonal transport alterations following platinum chemotherapy.…”
Section: Overview Of Axonal Degeneration In Cipnmentioning
confidence: 99%
“… 5 Similarly, in vitro data showed that bortezomib is also able to enhance tubulin polymerisation 16 and disrupt axonal transport, 17 while the non-neurotoxic proteasome inhibitor carfilzomib has no effect on microtubules at antineoplastic concentrations. 18 Further, bortezomib has been linked to delta 2 tubulin accumulation, altering microtubule stability and dynamics with consequent axonopathy and altered mitochondria motility. 19 Notably, neurographic in vivo molecular imaging demonstrated axonal transport alterations following platinum chemotherapy.…”
Section: Overview Of Axonal Degeneration In Cipnmentioning
confidence: 99%
“…It has now been demonstrated that bortezomib, a widely used 26S proteasomal subunit inhibitor, with anti-tumor activity in hematological malignancies, also has a stabilizing effect on MTs ( Staff et al, 2013 ; Meregalli et al, 2014 ; Malacrida et al, 2021 ). This effect can account for bortezomib anti-cancer activity.…”
Section: All Roads Lead To Microtubules: Targeting Microtubules But U...mentioning
confidence: 99%
“…It may be expected that the presence of MV1035 makes it difficult for the methylated nucleobase within DNA to reach the right site for the enzymatic reaction ( Figure 2 C,D). Noteworthy, the PBS for MV1035 within ALKBH2 was identified despite being partially closed and apparently inaccessible to the ligand (see Supplementary Figure S1 and Supplementary Table S2 ) thanks to SPILLO-PBSS’s ability to take into account protein flexibility [ 16 , 28 , 29 ].…”
Section: Resultsmentioning
confidence: 99%